2019
DOI: 10.1016/j.bbrep.2019.100625
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated-Akt overexpression is associated with a higher risk of brain metastasis in patients with non-small cell lung cancer

Abstract: Brain metastasis (BM) of non-small cell lung cancer (NSCLC) is relatively common and has a poor prognosis. Moreover, identifying which patients are more likely to develop BM is challenging. Akt, a serine/threonine-specific protein kinase, can be activated in various tumors, including lung cancer, and may be associated with poor prognosis. Here, we used immunohistochemistry to evaluate phosphorylated-Akt (p-Akt) expression in tumor tissues of 99 NSCLC patients. We also analyzed the genotype of the patients for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…Akt signaling plays an important role in cancer survival, proliferation and metastasis [ 11 ]. Akt signaling is commonly deregulated in cancers; in particular, Akt is overactivated in human lung cancer [ 45 ]. Akt, a serine/threonine kinase, is phosphorylated and activated by several external stimuli through transmembrane proteins, including receptor tyrosine kinases, integrins and cytokine receptors [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Akt signaling plays an important role in cancer survival, proliferation and metastasis [ 11 ]. Akt signaling is commonly deregulated in cancers; in particular, Akt is overactivated in human lung cancer [ 45 ]. Akt, a serine/threonine kinase, is phosphorylated and activated by several external stimuli through transmembrane proteins, including receptor tyrosine kinases, integrins and cytokine receptors [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the hub gene PPL, the corresponding protein was reported to interact with AKT1 protein (van den Heuvel et al, 2002;Wang et al, 2008), suggesting its possible role as a localization signal in AKT1-mediated signaling. Notably, many studies have shown that aberrant Akt activation is associated with the development of many tumors (Steelman et al, 2008;Jin et al, 2019). Both David et al (2004) and Lim et al (2007) reported that p-Akt overexpression can be used as an indicator of poor prognosis in NSCLC.…”
Section: Gene Module Analysismentioning
confidence: 99%
“…EPS8 is a crucial molecule that mediates EGFR-induced activation of Akt (Innocenti, 2003) and PPL proteins as a localization signal in AKT1-mediated signaling by interacting with AKT1 (van den Heuvel et al, 2002;Wang et al, 2008). Akt activation is well known to be associated with the development of many tumors (Steelman et al, 2008;Jin et al, 2019), and it can also prevent FoxO3a, a tumor suppressor, from binding to EPS8. Moreover, it was reported that EGFR, via a U0126-sensitive ERK1/2 pathway, controls the transcriptional upregulation of SCN9A to promote cellular invasion in NSCLC cell lines (Campbell et al, 2013).…”
Section: Survival Analysismentioning
confidence: 99%
“…Therefore, treatment of patients with NSCLC and BMs is a major concern for patients and clinicians 23 . BM is one of the most challenging aspects of the clinical treatment of NSCLC patients 24 . In the examined trials, 7–13,15‐21 BM incidence was lower in the PCI than in the control group (0–20.3% vs 11–54%).…”
Section: Discussionmentioning
confidence: 96%
“…23 BM is one of the most challenging aspects of the clinical treatment of NSCLC patients. 24 In the examined trials, [7][8][9][10][11][12][13][15][16][17][18][19][20][21] BM incidence was lower in the PCI than in the control group (0-20.3% vs 11-54%). The study, RTOG 0214, 9 Eight studies on OS were included in this meta-analysis, and all found that PCI did not affect the survival rate of NSCLC.…”
Section: Discussionmentioning
confidence: 99%